2015
DOI: 10.1038/srep12983
|View full text |Cite
|
Sign up to set email alerts
|

The selective post-translational processing of transcription factor Nrf1 yields distinct isoforms that dictate its ability to differentially regulate gene expression

Abstract: Upon translation, the N-terminal homology box 1 (NHB1) signal anchor sequence of Nrf1 integrates it within the endoplasmic reticulum (ER) whilst its transactivation domains [TADs, including acidic domain 1 (AD1), the flanking Asn/Ser/Thr-rich (NST) domain and AD2] are transiently translocated into the ER lumen, whereupon the NST domain is glycosylated to yield an inactive 120-kDa glycoprotein. Subsequently, these TADs are retrotranslocated into extra-luminal subcellular compartments, where Nrf1 is deglycosylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
116
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(142 citation statements)
references
References 60 publications
26
116
0
Order By: Relevance
“…The ER-targeting NTD of Nfe2l1 enables it to be topologically anchored within and around the membranes (56)(57)(58), whilst its NST glycodomain facilitates its proper protein folding and subsequent processing (59)(60)(61). The membrane-topology of Nfe2l1 determines its selective proteolytic processing by proteasomes and/or other cytosolic proteases in close proximity to the ER, in order to yield distinct lengths of its isoforms, before its mature CNC-bZIP factor is translocated into the nucleus (44,61,62). Such the membrane-bound Nfe2l1 factor can also be activated in the unfolded protein response to the ER stress stimulated by tunicamycin (to inhibit its N-linked glycosylation) (38), in addition to its proteasomal 'bounce-back' response (63,64).…”
Section: Synergism Of Mouse Nfe2l1 Nrf1 Nfe2l2mentioning
confidence: 99%
“…The ER-targeting NTD of Nfe2l1 enables it to be topologically anchored within and around the membranes (56)(57)(58), whilst its NST glycodomain facilitates its proper protein folding and subsequent processing (59)(60)(61). The membrane-topology of Nfe2l1 determines its selective proteolytic processing by proteasomes and/or other cytosolic proteases in close proximity to the ER, in order to yield distinct lengths of its isoforms, before its mature CNC-bZIP factor is translocated into the nucleus (44,61,62). Such the membrane-bound Nfe2l1 factor can also be activated in the unfolded protein response to the ER stress stimulated by tunicamycin (to inhibit its N-linked glycosylation) (38), in addition to its proteasomal 'bounce-back' response (63,64).…”
Section: Synergism Of Mouse Nfe2l1 Nrf1 Nfe2l2mentioning
confidence: 99%
“…The plasmid pcDNA-Flag-OGT (#29760) and the pRL-CMV reporter were purchased from Addgene and Promega, respectively. Additional expression constructs for Nrf1 and its mutant that had been created on the base of pcDNA3.1/V5His, as well as pcDNA-3 Â HA-Ub and the ARE-driven reporter gene P SV40 6 Â ARE-GSTA2-Luc, were developed in our laboratory [34][35][36][37][38][39]. All these constructs were verified by DNA sequencing.…”
Section: Plasmids and Sirnasmentioning
confidence: 99%
“…Conversely, a loss of the NST domain (aa 299-400, lanes #4 with 1.00/0.37), but not of the AD2 regions (aa 403-455, lanes #5 & 6), caused an apparent enhancement in OGT-mediated destabilization of the Nrf1 D299À440 mutant by $42%, when compared with the wild-type Nrf1 protein. Furthermore, our previous work has showed that the NST domain of Nrf1 is N-glycosylated and also enables it to be anchored within the ER lumen and, hitherto demonstrated that the process controls its topovectorial repartitioning out of the organelle [34][35][36][37][38][39]. Together, our findings suggest that the NST glycodomain of Nrf1 contributes to stabilization of its wild-type protein possibly through a mechanism that negatively monitors the repositioning of NST-flanking regions (aa 454-488 and 81-291) from the ER lumen into the cyto/nucleoplasmic compartments, such that both regions would be allowed for association with the OGT-mediated event for O-GlcNAcylation.…”
Section: O-glcnacylation Of Nrf1 Is Associated With Its Serine-rich Pmentioning
confidence: 99%
See 2 more Smart Citations